1984
DOI: 10.1038/308544a0
|View full text |Cite
|
Sign up to set email alerts
|

Experimental metastasis correlates with cyclic AMP accumulation in B16 melanoma clones

Abstract: Metastasis is a complex process whereby tumour cells from a primary neoplastic growth disseminate throughout the body and establish secondary tumour foci in distant organs. Biochemical traits associated with, or essential for, the expression of the metastatic phenotype have not yet been identified. In the course of examining stimulation of the B16 murine melanoma adenylate cyclase by melanocyte-stimulating hormone (MSH) and by the diterpene forskolin, we noted that tumour cell clones isolated from common paren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 22 publications
4
42
0
Order By: Relevance
“…In an earlier investigation we examined the responsiveness of a series of B16 melanoma clones with different metastatic capacities to stimulation by MSH and forskolin (Sheppard et al, 1984). Based on the accumulation of cAMP following exposure to these agents, it was found that the B16 melanoma cell clones segregated into high and low responders.…”
Section: Discuss I 0 Nmentioning
confidence: 98%
See 1 more Smart Citation
“…In an earlier investigation we examined the responsiveness of a series of B16 melanoma clones with different metastatic capacities to stimulation by MSH and forskolin (Sheppard et al, 1984). Based on the accumulation of cAMP following exposure to these agents, it was found that the B16 melanoma cell clones segregated into high and low responders.…”
Section: Discuss I 0 Nmentioning
confidence: 98%
“…Clones were isolated as described . From a panel of over 30 B16 melanoma clones that had been characterized in terms of their hormonal responsiveness and metastatic capacity (Sheppard et al, 1984), 5 were chosen for detailed analysis of adenylate cyclase func-…”
Section: Cell Culturesmentioning
confidence: 99%
“…Compared with normal cells, lower cAMP concentrations were found in certain tumor cells, which revealed that cAM Phas a negative role in cell proliferation (30). Additionally, intracellular cAMP levels were reported to be associated with the metastatic ability of tumor cells (31,32). Epidermal growth factor signaling has been well studied with regards to controlling cell proliferation, differentiation and migration (33).…”
Section: Discussionmentioning
confidence: 99%
“…However, a-MSH is reported to both stimulate and inhibit melanoma invasion in vitro and in vivo. Murine melanoma cells respond to a-MSH stimulation in vitro with a higher number of metastases in vivo, and a positive correlation exists between murine melanoma cell response to a-MSH (assessed by cAMP elevation) in vitro and metastatic success in vivo (Sheppard et al, 1984;Hill et al, 1990). However, a-MSH can inhibit B16-BL6 melanoma invasion through reconstituted (Matrigel) basement membrane (Murata et al, 1997), and reduce colony formation by 50%, in agreement with similar work in B16-F10 cells (Kameyama et al, 1990).…”
mentioning
confidence: 99%